Peningkatan Ketepatan Pendataan Lne Stop Guna Menurunkan Loss Time pada Proses Assembly Drive Chain dan Cam Chain di PT. XYZ - Marvin Reza Widjaja; Prayonne Adi (Jurnal Titra, 2018)
This study is accomplished to indentify the root causes of not accurate line stop data which recorded in daily operator report with the actual condition in assembly process of PT. XYZ. The difference makes PT. XYZ can not do the corrective action on line stop problem. The accuracy of data collection is expected to reduce the loss time that caused by line stop. This study is applied a cause and effect diagram and pareto chart, to describe and prioritize the root cause. The improvement are to apply a timepiece and a working instruction of line stop data collection. The results of improvement’s implementation was positive and line stop data collection becomes more accurate. The total loss time error before improvement is more than 20 minutes, now becomes less than 20 minutes.